Prevalence of Coronavirus infection and its relationship with vaccionation - Spilere, Amanda Regina; Peder, Leyde Daiane de (Research, Society and Development, 2023)
This study investigated the prevalence of COVID-19 in Três Barras do Paraná between 2021 and 2022, analyzing epidemiological data. Using a retrospective, cross-sectional, and descriptive approach, information was collected from public secondary sources such as the Epidemiological Information System. The results highlighted that the incidence of COVID-19 was most significant between June and September, representing nearly half of the cases. Notably, the majority of patients were asymptomatic, accounting for 83% of cases. Demographic analysis revealed a higher notification of the disease among women, with 2,080 notifications compared to 1,120 in men. The age group of 50 to 69 years represented 40% of the reported cases. Only 10% of notified patients had comorbidities. Vaccination played a crucial role in reducing the incidence of the disease. In the first half of 2021, approximately 7,300 people received the first dose, with a high rate of completion of the initial vaccination schedule. The analysis showed a significant decrease in the prevalence of infection after vaccination. In the second half of 2021, there was a 10% reduction in the number of doses administered compared to the first half, but the decrease in the prevalence of infection was even more evident, with a 39% drop in positive cases after vaccination. In summary, this study highlights the importance of vaccination in reducing the incidence of COVID-19 and provides valuable information about the epidemiological characteristics of the affected population in Três Barras do Paraná. High vaccination adherence and the decrease in infection prevalence indicate that vaccines play a fundamental role in containing the virus’s spread. However, it is crucial to continue monitoring and adapting vaccination strategies as the pandemic situation evolves.